(5w+6)(5w-6)=

Simple and best practice solution for (5w+6)(5w-6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5w+6)(5w-6)= equation:


Simplifying
(5w + 6)(5w + -6) = 0

Reorder the terms:
(6 + 5w)(5w + -6) = 0

Reorder the terms:
(6 + 5w)(-6 + 5w) = 0

Multiply (6 + 5w) * (-6 + 5w)
(6(-6 + 5w) + 5w * (-6 + 5w)) = 0
((-6 * 6 + 5w * 6) + 5w * (-6 + 5w)) = 0
((-36 + 30w) + 5w * (-6 + 5w)) = 0
(-36 + 30w + (-6 * 5w + 5w * 5w)) = 0
(-36 + 30w + (-30w + 25w2)) = 0

Combine like terms: 30w + -30w = 0
(-36 + 0 + 25w2) = 0
(-36 + 25w2) = 0

Solving
-36 + 25w2 = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '36' to each side of the equation.
-36 + 36 + 25w2 = 0 + 36

Combine like terms: -36 + 36 = 0
0 + 25w2 = 0 + 36
25w2 = 0 + 36

Combine like terms: 0 + 36 = 36
25w2 = 36

Divide each side by '25'.
w2 = 1.44

Simplifying
w2 = 1.44

Take the square root of each side:
w = {-1.2, 1.2}

See similar equations:

| -X+2x^2=0 | | -(8y+2)-(-7y-5)=-1 | | B=b+2a+3c | | 8(3x-8)=2(12x+7) | | (18y^2-12xy)-(6y^2+xy-a)= | | 3+3s-2=8s+5-3s | | 4(3w+1)+4v=4(v-6)-2v | | 6t+8t=84 | | 9ln(4x)=54 | | 6ay^3+5ay^2-4ay= | | (2.25c-9.28b+3.82a)-(-3.92a-1.72b-8.33c)= | | 2p=5p+9 | | 90=2x*3x+1+5*5 | | -8(3b+2)+(25b-9)=0 | | (23y^2+4y^3-12)-(11y^3-8y^2+y)= | | 3.1q-2.2-5.3q=-3.2q-1.2 | | 9+x^2=0 | | 39=x+5 | | 2.2q-4.7-4.5q=3.3q-3.7 | | 39=x+5*3 | | (2z+5c-3a)-(6a+2c-4z)= | | -3(x+4)+13=-2x-11 | | (y-z-b)-(b+y+z)= | | (7262x)+(1.26a)-(2844x-8.23a)= | | 2x^5+7x^4-10x^3-53x^2-28x+28= | | (72.62x)+(1.26a)-(2844x-8.23a)= | | 8(2x-9)=2(8x+6) | | 3x^3=32 | | 9+11z-3=5z+69-3z | | -3(x-1)-7=4x-11 | | 18+3y=9y | | (24.2x)+(8.25)+(83.6x-2.92)= |

Equations solver categories